Pengembangan Kualitas Pelayanan Jasa Pengiriman Barang pada PT Pos Indonesia (Persero) KCU Bandung - Zahra, Alisa; Herawaty, Tetty; MUttaqin, Zaenal (Universitas Sam Ratulangi, 2024)
The development of service quality in logistics companies relies on policies, strategies, planning, and preparing Standard Operating Procedures. PT Pos Indonesia is currently competing with rival companies. So, companies must provide the best service to provide satisfaction to consumers. This research aims to determine the quality of service at PT Pos Indonesia KCU Bandung. This research uses descriptive qualitative research methods. Data collection in this research carried out observations and interviews. The data analysis used is descriptive, SWOT analysis, IFAS analysis, and EFAS analysis. Based on the research conducted, it can be seen that the quality of service at PT Pos Indonesia KCU Bandung has been carried out well. PT Pos Indonesia has an SOP for sending goods and a system for resolving consumer complaints through the Customer Complaint Handling application. Based on the IFAS and EFAS analysis, it can be seen that PT Pos Indonesia KCU Bandung is in the quadrant I position, which means that the company has great strength to take advantage of existing opportunities.